Novel Bioactive Peptides from Red Bigeye (Priacanthus macracanthus) Flesh Protein - Mohamed, Nor Salasiah; Amin, Amiza Mat; Ahmad, Fisal (Malaysian Applied Biology, 2024)
Red bigeye (Priacanthus macracanthus) is a common fish species in Malaysia. This study reported an in silico assessment of the main proteins in red bigeye flesh as precursors for bioactive peptides. Six major proteins were chosen as precursors from the proteomic profiles of red bigeye proteins. Analyses using the BIOPEP-UWM database found that Protein number 4 gave the highest total number of bioactive peptides (5052 peptides), with dominant bioactivity in angiotensin-I-converting enzyme (ACE) inhibition (1571 peptides) and dipeptidyl peptidase-IV (DPP-IV) inhibition (2238 peptides). The ACE inhibitors had a frequency of bioactive fragment occurrences (A) of 0.4098, while the DPP-IV inhibitors gave a frequency of 0.5805. In silico proteolysis using BIOPEP-UWM found that pepsin (pH > 2) was the most promising proteinase in releasing a high number of DPP-IV and ACE inhibitory peptides. A novel peptide with significant potential was identified as QYKF. This study shows that red bigeye is a potential source of antihypertensive and antidiabetic peptides.